Tema dan Nilai Moral dalam Karya Sastra Melayu Klasik “Hikayat Hang Tuah, Hikayat Raja Pasai, dan Hikayat Abdullah “ - Anisa Putri; Arvirelia Rahmatillah; Feby Oriza Sativa; Isfy Aprilian Nusen; Maya Aulia Sari; Vera Sardila (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This discussion examines the themes and values ​​contained in classical Malay literary works focusing on several main works such as "Hikayat Hang Tuah", Hikayat Raja Pasai", "Hikayat Abduallah". The purpose of this writing is to identify and analyze main themes, such as heroic love, morality, religion and socio-politics, as well as values ​​that include moral, social, cultural and religious. Analysis is carried out to understand the relationship between themes and values ​​and the historical and cultural context of the time. In this article we will compare the themes and values ​​between the works to find significant similarities and differences. Classical Malay literary works not only function as entertainment, but classical Malay literary works also serve as ethical and moral guidelines that are relevant today. These works reflect the classical Malay community's view of life and provide an important contribution to the moral and cultural identity of the Malay community. This discussion emphasizes the importance of understanding and preserving the heritage of classical Malay literature to create insight into the culture and history of the archipelago.